2004
DOI: 10.1117/12.565765
|View full text |Cite
|
Sign up to set email alerts
|

Plant pigment types, distributions, and influences on shallow water submerged aquatic vegetation mapping

Abstract: Development of robust protocols for use in mapping shallow water habitats using hyperspectral imagery requires knowledge of absorbing and scattering features present in the environment. These include, but are not limited to, water quality parameters, phytoplankton concentrations and species, submerged aquatic vegetation (SAV) species and densities, epiphytic growth on SAV, benthic microalgae and substrate reflectance characteristics. In the Indian River Lagoon, Fl. USA we conceptualize the system as having thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…, 2008), despite interactions with the water column itself (Holden & LeDrew, 2001; Han, 2002; Bostater et al. , 2003; Hall et al. , 2004), which obscures the characteristic SAP spectral patterns.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…, 2008), despite interactions with the water column itself (Holden & LeDrew, 2001; Han, 2002; Bostater et al. , 2003; Hall et al. , 2004), which obscures the characteristic SAP spectral patterns.…”
Section: Introductionmentioning
confidence: 99%
“…Imaging spectroscopy (also called hyperspectral remote sensing) measures hundreds of contiguous narrow bands spanning the solar reflective spectrum from 400 to 2500 nm. The result is a nearly continuous spectrum measured in each pixel that provide the information needed to detect SAPs in the water column (Zhang et al, 1997;Underwood et al, 2006;Hestir et al, 2008), despite interactions with the water column itself (Holden & LeDrew, 2001;Han, 2002;Bostater et al, 2003;Hall et al, 2004), which obscures the characteristic SAP spectral patterns. When plant species are spectrally distinct (Fyfe, 2003), imaging spectroscopy is a likely method for mapping SAPs down to species level .…”
Section: Introductionmentioning
confidence: 99%
“…6,8 A basic principle in remote sensing is that features of interest reflect or emit light in uniquely different ways and these differences can be detected and recorded by the remote sensing system. 9,10,11 Our experience has shown that one of the major issues hindering the scientific utility and application of hyperspectral data to resource mapping is the uncertainty or error that exists when attempting to link ground truth data with spectra extracted from pixels in the image cube. Hyperspectral images collected from aircraft using line scanning systems such as PHILLS or AISA often contain significant spatial error as a result of aircraft pitch, roll and yaw making direct comparisons between ground truth data and individual pixels difficult or even impossible.…”
Section: Cape Cãñaverãlmentioning
confidence: 99%
“…Hyper‐spectral imaging involves a relatively high‐resolution spectrum (wavelengths of 2–10 nm) being collected for each pixel in the image. Hyper‐spectral imaging allows for the estimation of the content of chlorophyll‐ a and other cyanobacterial pigments in water bodies (Hall, Bostater, & Virnstein, 2004; Hunter, Matthews, Kutser, & Tyler, 2017; Hunter, Tyler, Carvalho, Codd, & Maberly, 2010). It is also possible, with appropriate algorithms, to separate different cyanobacterial genera using this technology (Kudela et al., 2015).…”
Section: Monitoring Sampling and Sample Analysismentioning
confidence: 99%